Pendampingan Literasi Digital Anti Bullying Bagi Siswa SMKN 2 Garut - Milyane, Tita Melia; Syifaa, Muhamad Armien; Widyaningrum, Septiana Yustika; Aliffaza, Robby; Natasha, Janice; Gathan, Muhammad (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2025)
Digital literacy is a crucial competency in the current era of digitalization and globalization. The development of digital literacy skills is a strategic effort to empower Generation Z in utilizing social media as a window of information. This community service program is carried out with the aim of increasing digital literacy among students in grades 10 and 11 of SMKN 2 Garut as generation Z teenagers who utilize digital media in their daily lives. The methods used include mentoring and education activities regarding digital literacy, with a focus on the wise use of social media to prevent cyberbullying and the spread of hoax news. This program involves 100 students as target partners who participate in mentoring activities for one day. The result of this activity is to gain understanding so that a discussion space is created about the importance of the dangers of cyberbullying and the spread of hoax news to be able to counteract the bad impact of social media.